Working memory training: Taking a step back to retool and create a bridge between clinical and neuroimaging research methods. Issue 6 (2nd November 2022) - Pappa, Katerina; Flegal, Kristin E.; Baylan, Satu; Evans, Jonathan J.
Abstract: Improvements in patient outcomes and mortality after brain injury alongside increasing ageing population have resulted in an increasing need to develop cognitive interventions for individuals experiencing changes in their cognitive function. One topic of increasing research interest is whether cognitive functions such as attention, memory and executive functioning can be improved through the use of working memory training interventions. Both clinical and neuroimaging researchers are working to evidence this, but their efforts rarely come together. We discuss here several issues that may be hindering progress in this area, including the tools researchers utilize to measure cognition, the choice between employing active or passive control groups, the focus on transfer effects at the expense of well-characterized training effects, and the overall lack of neuroimaging studies in individuals with neurological disorders. We argue that the only way to advance the field is to build bridges between the disciplines of clinical neuropsychology and cognitive neuroscience. We suggest a multi-level framework to validate the efficacy of working memory interventions and other forms of cognitive training that combine both clinical and neuroimaging approaches. We conclude that in order to move forward we need to form multidisciplinary teams, employ interdisciplinary methods, brain imaging quality rating tools and build national and international collaborations based on open science principles.